Building the corporate image of Grand Dafam Rohan Syariah Hotel through the use of Instagram - Budi Setiawan (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2021)
Social media can be a solution for companies in branding their products. One argument is that social media can generate engagement around a brand, create a community, and serve as a customer support channel. Social media helps businesses to interact with a diverse range of stakeholders. The purpose of this study was to examine the role of the social media platform Instagram in shaping the corporate image of a hotel in Yogyakarta, Indonesia. The study used a descriptive qualitative method, with data collection tools including interviews, observations, and a library study. The research shows that Grand Dafam Rohan Syariah uses a strategy to promote its hotel by utilizing social media Instagram in carrying out its promotional activities. It used Instagram to form an image by introducing symbols and programs. The hotel's social media Instagram communicates the brand message and builds people's perceptions after seeing the postings on its Instagram accounts. However, as a new hotel, it takes time to achieve what the company expects. Thus, consistency is the key to the Grand Dafam Rohan hotel realizing its goals. Besides, there are other strategies that management should do to support all image-building programs.